2017
DOI: 10.1016/j.biopsycho.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Atypical interference control in children with AD/HD with elevated theta/beta ratio

Abstract: The theta/beta ratio (TBR) is a major area of interest within electroencephalogram (EEG) research in AD/HD. While researchers suggest a prognostic role for TBR in AD/HD, its relationship to behavior remains uncertain. Recent evidence suggests that elevated TBR in AD/HD may be related to atypical inhibition, particularly at an attentional level. This study aimed to examine the performance on three inhibitory tasks of children with AD/HD. Fifty-eight children with AD/HD participated, divided into an elevated TBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…TBRs calculated with standardized frequency bands on eyes-closed (Zhang et al, 2017, Clarke et al, 2011. These TBR values are slightly different, however we assume the trends in distribution and clustering observed should be consistent.…”
Section: Assumptions and Limitationsmentioning
confidence: 85%
See 3 more Smart Citations
“…TBRs calculated with standardized frequency bands on eyes-closed (Zhang et al, 2017, Clarke et al, 2011. These TBR values are slightly different, however we assume the trends in distribution and clustering observed should be consistent.…”
Section: Assumptions and Limitationsmentioning
confidence: 85%
“…The arbitrariness of the TBR threshold values and the heterogeneity of methods employed certainly cast doubt on these decisions and calls for a sophisticated validation of the existence of a subgroup of ADHD patients with high TBRs, as well as the value of the threshold that separates these subgroups. Although previous literature points towards a cluster of ADHD patients with an increased TBR (Zhang et al, 2017, Clarke et al, 2011, no study has investigated the existence of clusters based solely on TBRs. The existence of two distinct ADHD subgroups, defined specifically by high or low TBR values needs to be validated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the theta/beta ratio may actually be more strongly associated with an alternate aspect of cognitive processing than the low-level discriminant processing assessed by the auditory oddball task in these studies. For instance, Zhang et al 40 examined whether there was a relationship between the elevated theta/beta ratio in children with ADHD and varying types of inhibition. Zhang et al 40 found that those children with both ADHD and enhanced theta/ beta ratios, had significantly larger reaction times in the interference control task relative to the control group.…”
Section: Discussionmentioning
confidence: 99%